Analysis of Speaking Learning Strategies Used by Introvert Students - Kuning, Dewi Sri; Prihatmojo, Agung (Juwara: Jurnal Wawasan dan Aksara, 2025)
Speaking strategy is a method taken by language learners to solve problems when learning to speak. Speaking learning strategies have two types, namely direct speaking learning strategies which consist of memory strategies, cognitive strategies and compensatory strategies, while indirect speaking learning strategies consist of metacognitive strategies, affective strategies and social strategies. The use of speaking strategies is widely used by language learners, including language learners who have introverted personalities. Introverted personalities usually tend to prefer doing things themselves, focusing more on their own thoughts. The aims of this research to analyze the speaking learning strategies used by introvert students.  This research uses qualitative research methods by taking five introverted based on the results of the MBTI test. Researchers used interviews and questionnaires as data collection techniques. The research results showed that introverted students used four speaking strategies, namely memory strategies, cognitive strategies, compensatory strategies and meta-cognitive strategies. The research results also show that cognitive strategies and compensatory strategies are the strategies most frequently used by introverted students from the 4th semester English education study program in Universitas Muhammadiyah Kotabumi.